<span><span><span><span>2x</span>+y</span>+<span>−y</span></span>=<span>6+<span>−y</span></span></span><span><span>2x</span>=<span><span>−y</span>+6</span></span>Step 2: Divide both sides by 2.<span><span><span>2x</span>2</span>=<span><span><span>−y</span>+6</span>2</span></span><span>x=<span><span><span><span>−1</span>2</span>y</span>+3</span></span>Answer:<span> x=<span><span><span><span>−1</span>2</span>y</span>+3</span></span>
x-3=-2
x-3+3=-2+3
answer x=1
Yes i need help on a problem, can i message you?
Answer:
49 and 58
Step-by-step explanation:
pls brainliest
Answer:
-24
Step-by-step explanation:
plz mark brainlyest
To me it sounds like 4 divided by n +5